OPTIMASI LOKASI DEPO DAN ALOKASI BUS PADA SETIAP DEPO SERTA RUTE DI PERUM PPD JAKARTA - Abd. Aziz (NIM 23494019), RZ
Abstract : Perum PPD as one of operator in Jabotabek transportation system endeavors to increase its income by perform a project of bus repooling to minimize its total costs. Because to perform the bus repooling involves many aspects, so it is needed a good research to overcome some constraints in trial technique who performed by Perum PPD. This research was depeloped a computation model to determine quantity of bus in each route and efficiency of depot\'s location and allocation number of bus in each depot, optimation of depot\'s location and allocation number of bus in each depot. The solution is performed based on criteria of minimize total costs consisting of non-productive transportation costs, depot\'s fixed costs and depot\'s operational costs per bus. The result shows that from 14 of existing depots, there were only 10 depots which in active, they include depots A, D, E, F, H, J, K, M, N, and P with total costs are Rp 107,373,951.00 daily, consisting non-productive transportation costs are Rp 7,495,262.00 daily, total depot\'s fixed costs are Rp 1,235,979.00 daily and total depot\'s operational costs per bus are Rp 98,642,710.00 daily.